Unconscious processing of facial race and emotional information - Zhi Quan; Xinchao Yang; Wenpei Pan; Ruoxi Wang; Danyang Cui; Qiang Xu (BMC Psychology)
Abstract Facial information plays a significant role in social interactions. However, the extent to which racial information and emotional information in faces can be processed under unconscious conditions has been a matter of debate. This study utilized the breaking Continuous Flash Suppression (b-CFS) paradigm to investigate whether racial information and emotional information in faces could be processed unconsciously, and whether these different types of information might influence each other. By comparing the suppression-breaking response times of angry, neutral, and happy faces across same-race and cross-race conditions, our findings revealed that participants exhibited significantly shorter response times for cross-race faces compared to same-race faces, indicating an unconscious processing advantage for cross-race stimuli. Furthermore, angry and happy faces demonstrated significantly shorter suppression-breaking response times than neutral faces, with happy faces breaking suppression faster than angry faces. Importantly, for same-race faces, the response times for angry and happy faces were shorter compared to neutral faces. But for other-race faces, happy faces exhibited a significantly shorter response times compared to both neutral and angry faces, while there was no significant difference between neutral and angry faces. These results suggested that both racial and emotional information could be processed unconsciously, and that these two types of information could influence each other under unconscious conditions.